2005
DOI: 10.1007/s00204-005-0009-5
|View full text |Cite
|
Sign up to set email alerts
|

Zinc: a multipurpose trace element

Abstract: Zinc (Zn) is one of the most important trace elements in the body and it is essential as a catalytic, structural and regulatory ion. It is involved in homeostasis, in immune responses, in oxidative stress, in apoptosis and in ageing. Zinc-binding proteins (metallothioneins, MTs), are protective in situations of stress and in situations of exposure to toxic metals, infections and low Zn nutrition. Metallothioneins play a key role in Zn-related cell homeostasis due to their high affinity for Zn, which is in turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
256
2
22

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 388 publications
(284 citation statements)
references
References 82 publications
4
256
2
22
Order By: Relevance
“…High levels of selenium are found in brazil nuts, kidney, seafood and cereals, although this is soil dependent and it has been reported that European intake of selenium is falling [31]. Zinc acts as a co-factor for enzymes promoting DNA transcription and protein synthesis [32], has a role in expression of steroid hormone receptors [33] and has anti-apoptotic [34] and anti-oxidant properties [35]. Studies have demonstrated that a zinc deficiency can lead to subfertility and abnormal reproductive outcomes [36], and to pregnancy complications [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of selenium are found in brazil nuts, kidney, seafood and cereals, although this is soil dependent and it has been reported that European intake of selenium is falling [31]. Zinc acts as a co-factor for enzymes promoting DNA transcription and protein synthesis [32], has a role in expression of steroid hormone receptors [33] and has anti-apoptotic [34] and anti-oxidant properties [35]. Studies have demonstrated that a zinc deficiency can lead to subfertility and abnormal reproductive outcomes [36], and to pregnancy complications [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is an important trace element in organisms and it is essential as a structural or catalytic constituent of many proteins and enzymes (Stefanidou et al 2006). Zinc is also an important element in preventing free radical formation and thus in protecting bodies from oxidative damage and in maintaining the immune functions.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc is a trace nutrient indispensable for organisms (Stefanidou et al 2006). Zinc homeostasis is mostly regulated by zinc transporters (Eide 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been undertaken to investigate the effects of zinc supplementation on various diseases or physiological conditions in elderly people or in subjects having dietary or biochemical zinc deficiency (Stefanidou et al, 2006). Most of these studies have been performed among hospitalized or institutionalized elderly or focussed mainly on the relationship between zinc status and immune function (Pepersack et al, 2001;Mitchell et al, 2003;Chandra, 2004), while data in elderly free living people are scarce.…”
Section: Discussionmentioning
confidence: 99%